2011
DOI: 10.1097/jgp.0b013e31820ee9ef
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Use of Tai Chi Chih Augments Escitalopram Treatment of Geriatric Depression: A Randomized Controlled Trial

Abstract: Background-Nearly two-thirds of elderly patients treated for depression fail to achieve symptomatic remission and functional recovery with first-line pharmacotherapy. In this study, we ask whether a mind-body exercise, Tai Chi Chih (TCC), added to escitalopram will augment the treatment of geriatric depression designed to achieve symptomatic remission and improvements in health functioning and cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
208
1
16

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(262 citation statements)
references
References 59 publications
3
208
1
16
Order By: Relevance
“…Studies have used different exercise types, such as strength training, 23,24 tai chi chih, 21 and combined exercise (strength, aerobic, balance, and flexibility). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have used different exercise types, such as strength training, 23,24 tai chi chih, 21 and combined exercise (strength, aerobic, balance, and flexibility). …”
Section: Discussionmentioning
confidence: 99%
“…15,20 Few studies have included older individuals with a clinical diagnosis of major depression and AD. [21][22][23][24][25][26] Although data about this association are scarce, previous reviews concluded that the differences in exercise type and QoL evaluations might have affected comparisons between studies. 27,28 Moreover, some of those reviews included adults in general and analyzed other variables, in addition to QoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De las doce intervenciones analizadas, cuatro de ellas (Hernández-Reif, Field & Thimas, 2001;Hoffmann-Smith et al, 2009;Jahnke et al, 2010;Wall, 2005) abordaron el problema de forma secundaria como un parámetro más dentro de su objetivo de investigación y sin utilizar un instrumento de evaluación específico para el sueño; cinco (Caldwell et al 2009;Hosseini et al, 2011;Lavretsky et al, 2011;Taboonpong et al, 2008;Wang et al, 2010), aunque sí utilizaron un instrumento específico de evaluación, abordan la evaluación de forma general sin describir sobre qué aspectos o parámetros del sueño se produjo la mejora; y tres (Irwin et al, 2008;Li et al, 2004;Yeh et al, 2008) analizaron los efectos del TCC sobre los trastornos de sueño en profundidad, con instrumentos específicos y diferenciando los aspectos de mejora. a) Estudios que no utilizan instrumentos de medición específicos para el sueño.…”
Section: Resultsunclassified
“…태극권의 경우에도 불안 및 우울감의 감소 [9,10], 혈압감소 [11], 노인 낙상의 감소 [12], 골다 공증 유병율 감소등 [13], 심혈관계 위험인자의 개선 등이 보고된 바 있다 [14,15] (Table 1). 참고 문헌 …”
unclassified